Adelosgryllus rubricephalus: A new genus and species of cricket (Orthoptera : Phalangopsidae) - Mesa, A.; Zefa, E. (Entomological Society Brasil, 2004)
Adelosgryllus rubricephalus, a new genus and species of phalangopsid cricket are described. Illustrations of male and female specimens as well as descriptions of phallic sclerites, chromosomes and geographical known distribution are furnished. A discussion on the species taxonomic status of this cricket within the family is also included.
Keywords: Grylloidea; morphology; phallic sclerite; chromosome